Charge Tranport: Flickering Polarons Extending over Ten Nanometres Mediate Charge Transport in High‐Mobility Organic Crystals (Adv. Theory Simul. 9/2020). Issue 9 (7th September 2020) - Giannini, Samuele; Ziogos, Orestis George; Carof, Antoine; Ellis, Matthew; Blumberger, Jochen
Abstract : Charge transport in organic semiconductors is often described by localized charge hopping or band‐theory models. In article number 2000093, using advanced atomistic computer simulations, Jochen Blumberger and co‐workers show that in high‐mobility organic semiconductors, charge carriers form flickering polarons—highly dynamic quantum objects delocalized over many molecules but finite in size due to thermal disorder.